Potential of Thibbun Nabawi Habbatusauda (Nigella sativa); Review of the Active Pharmacological Timoquinone - Mardan, Mardan; Ismail, Isriany; Rauf, Afrisusnawati (Universitas Islam Negeri Alauddin Makassar, 2021)
Habbatusauda or Black Seed or Black Cumin (Nigella sativa) has been widely mentioned in various Islamic studies, including its potential as a